Regulatory mechanisms underlying functional maturation of Sertoli cells in response to androgens during postnatal development - Edelsztein, Nadia Yasmín (2019)
Androgen-dependent maturation ofSertoli cells during postnatal testicular development is key for the establishmentof spermatogenesis. Meiosis in the male begins at puberty and relies onandrogens and retinoic acid. Immature Sertoli cells produce high levels of AMH,which is inhibited by androgens at puberty. The molecular mechanisms underlyingandrogen-mediated AMH decline are unknown. CYP26B1 degrades retinoic acid inthe prenatal testis preventing meiosis initiation. The concurrence of meioticentry and Sertoli cell maturation in response to androgens led us to proposethat CYP26B1 ?like AMH? is downregulated by androgens in the Sertoli cellduring puberty, thus enabling meiosis initiation. By immunohistochemistry, wesaw that CYP26B1 expression declines in the postnatal mouse Sertoli cell asandrogen receptor (AR) expression increases, closely before meioticspermatocytes appear. Luciferase reporter assays in the SMAT1 Sertoli cell lineshowed a direct negative effect on Amh promoter activity in the presence ofdihydrotestosterone (DHT, P<0.001). Site-directed mutagenesis and ChIP-qPCRassays showed that androgen-mediated inhibition requires the SF1 sites in theAmh promoter. Regarding Cyp26b1, we saw no changes in promoter activity inresponse to androgens (P=0.34). This lack of response was further supported byinvariant levels of endogenous Cyp26b1 expression in SMAT1 cells transfectedwith the AR (P=1.0) and in primary Sertoli cells of 10-day-old mice in culture(P=0.7), after DHT treatment. ChIP-qPCR showed no enrichment in AR sequencesanalyzed, indicating a lack of functional binding of the AR. In sum, weconfirmed a negative correlation between the immature Sertoli cell markers AMHand CYP26B1 and AR expression and meiotic initiation in postnatal development.We identified the molecular mechanism underlying AMH inhibition by androgensbut found that the decline in CYP26B1 expression is not caused by a directinhibitory androgen effect on Sertoli cells.